GREEN ACCOUNTING DALAM PENELITIAN KEPUSTAKAAN - Tifany Citrayantie; Darwis Said; Mediaty Mediaty (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
To avoid overexploitation of nature in meeting the needs of human life, a country through its government issued rules related to the